KONSEP PEMASARAN AGRIBISNIS : PENDEKATAN EKONOMI DAN MANAJEMEN - Ratna Winandi Asmarantaka; Juniar Atmakusuma; Yanti Nuraini Muflikh; Nia Rosiana (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2017)
Agribusiness marketing approach can be done through economic or management approach. The economic approach shows the overall presence of marketing channels that will be more efficient and determined by the Structure Conduct and Performance (SCP). The higher the percentage of market share indicates the strength of an enterprise in an industry. If the market share is relatively small and diffuse then the market tends to be in a competitive market reflected by market conduct and market performance On the other hand, a marketing approach to management is a business strategy of a company (group) to improve the efficiency or profit of a company and its networking. Value chain, supply chain, governance value chain analysis is part of the overall agribusiness marketing analysis, so players who have dominant power or market share will be visible in the marketing channel and the centralized market structure. The cooperation of small firms whose market share is relatively dispersed, the market structure tends to lead to a perfectly competitive market with the performances delivered to the market mechanism.